Scenes of madness : a psychiatrist at the theatre - Davis, Derek Russell (Routledge, 1995)
Unlike the `textbook' description of mental illness, discusses an earlier tradition that led psychiatrists to turn to Shakespeare's plays for such models as Ophelia and Lear, to help them understand the madness observed in their patients.